Effect of NaCl and MgCl2 on the hydration of lime-pozzolan blend by recycling sewage sludge ash. (1st September 2021) - Zhou, Yifan; Lu, Jianxin; Li, Jiangshan; Cheeseman, Chris; Poon, Chi Sun
Abstract: An extensive amount of work has focused on investigating the effects of seawater as mixing water on the mechanical properties and durability issues of cement pastes/mortars/concrete especially with steel rebars. However, limited information was available for the effects of seawater on the microstructural properties and compositions of blended cement systems. Sewage sludge ash has been widely studied as a supplementary cementitious material to manage wastes more sustainably and to relieve the environmental burden. Therefore, this paper investigated the mechanical properties as well as the microstructural findings of the lime-sewage sludge ash binder under the effects of the most dominant ion (i.e. Cl − ) in seawater by mixing with NaCl and MgCl2 (major salts of seawater) solution respectively. The results reveal that as compared to the control, acceleration effects were remarkable in the NaCl mix and the total amount of heat evolved was increased by mixing with both single salts. The use of the concerned sea salts accelerated the setting and increased the compressive strength until curing for 28 days. But for the mix prepared with MgCl2, its strength was still significantly improved at 60 days. The formation of Friedel's salt in the mix prepared with NaCl was evidenced by X-ray diffraction and thermal gravimetry mainly due to the highest concentration of Cl − in NaCl. Also, the average pore diameter was decreased, and the finer fraction of pores was increased after the addition of NaCl and MgCl2, explaining their high strengths. Highlights: Effects of NaCl and MgCl2 on lime-SSA mix were separately studied. MgCl2 significantly reduced setting time and showed superior 7–60-d strength due to low pH and Mg(OH)2 precipitates. A very high concentration of Cl − in NaCl mix and formation of Friedel's salt accelerated hydration. Late-age strength was affected by percentage of fine porosity and reasonable pore size distribution. Recycling SSA in lime-pozzolan mix facilitates its sustainable management.